Leadership in Action : Dividends and Interest - Learning From Experience Bridges the Generations - Chappelow, Craig (Center for Creative Leadership, 2006)
When it comes to developing effective leaders, the most basic skill that can be taught is the willingness and ability to learn from whatever experiences life brings.